Aktivitas Ekstrak Metanol Daun Alang-Alang (Imperata cylindrica (L.) P. Beauv) sebagai Antinflamasi: Activity of Alang-Alang (Imperata cylindrica (L.) P. Beauv) Leaves Methanol Extract as Anti-inflammatory - Chairul Saleh; Marem Sestiani; Erwin Erwin (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
An anti-inflammatory activity test of methanol extract of alang-alang leaves (Imperata cylindrica (L.) P. Beauv) on protein denaturation inhibition in vitro was carried out. The purpose of this study was to determine the content of secondary metabolites and the anti-inflammatory activity of the methanol extract of alang-alang leaves. The method used is a qualitative test method based on staining to determine the content of secondary metabolites and an in vitro method using a protein in the form of Bovine serum albumin (BSA) which is induced by heat to determine the anti-inflammatory activity of methanol extract of Imperata leaves and diclofenac sodium as a positive control. results of the phytochemical screening showed that the methanol extract of Imperata leaves contained flavonoids, phenolics and steroids. Activity test of alang-alang leaf methanol extract in IC50 was 125.937 ppm. The methanol extract of alang-alang leaves has potential as an anti-inflammatory. Keywords: Imperata cylindrica (L.) P. Beauv, Alang-alang, Anti-inflammatory, In Vitro AbstrakUji aktivitas antiinflamasi ekstrak metanol daun alang-alang (Imperata cylindrica (L.) P. Beauv) terhadap penghambatan denturasi protein secara in vitro telah dilakukan. Tujuan penelitian ini adalah untuk menentukan kandungan senyawa metabolit sekunder dan aktivitas antiinflamasi ekstrak metanol daun alang-alang. Metode yang digunakan ialah metode uji kualitatif berdasarkan perwarnaan untuk menentukan kandungan metabolit sekunder dan metode in vitro menggunakan protein berupa Bovine serum albumin (BSA) yang diinduksi oleh panas untuk menentukan aktivitas antiinflamasi ekstrak metanol daun Alang-alang dan natrium diklofenak sebagai control positif. Hasil skrining fitokimia menunjukkan ekstrak metanol daun alang-alang mengandung flavonoid, fenolik dan steroid. Uji aktivitas ekstrak metanol daun alang-alang dalam IC50 adalah 125,937 ppm. Ekstrak metanol daun alang-alang memiliki potensi sebagai antiinflamasi. Kata Kunci: Imperata cylindrica (L.) P. Beauv, Alang-alang, Antiinflamasi, In Vitro